Students’ Achievement in Writing Analytical Exposition Text At Eleventh Grade Student of SMA N 8 Jambi City - Rahmayani Zain; Khidayatul Munawwaroh; Nurul Fitri (Universitas Batanghari Jambi, 2022)
This study aimed to find out students' achievement in writing analytical exposition text at the Eleventh Grade of SMAN 8 Jambi. This research took this title to find out what the student's lack of understanding the writing analytical exposition text and it is needed to know students' achievement in writing analytical exposition text as a learning tool to evaluate the learning process during pandemic covid-19. This research has 19 respondents and the methodology of this research is quantitative research. This study chose to research SMAN 8 Jambi because wanted to know students' achievement in writing analytical exposition text. In this research, there are three indicators of writing analytical exposition text were a thesis, argument, and reiteration. The student has the writing test based on the topic by This research and writes it with three indicators of analytical exposition text. From the result, This research found that there were 7 or 36,8% of the students who got a very good and good score. It means that there were students who got a standardized score from their test. 2 or 10,6% is for the students who got a fair score. And the last, 3 or 15,8% for the students who got the poor score. It means that there were students who suggest retaking or considered failing the test.